Entendendo a desproporcionalidade de macroinvertebrados aquáticos em relações tamanho-densidade em riachos de Mata Atlântica - Braga, Julia Maria (Universidade Federal de São Carlos, 2024)
Metabolic Theory is one of the main theories used to understand trophic networks and energy flows in ecosystems. In general, a decrease in population density is expected as the individual body size of species increases, thus sustaining the flow of energy that should flow from smaller to larger organisms. In this study, we sought to understand the disproportionality in size-density relationships of macroinvertebrates observed in Atlantic Forest streams, potentially influenced by the functional singularities of the taxa. To this end, the positive residuals of the SDR (size-density relationship) were calculated and the functional characteristics of each species were compiled in order to find a relationship between greater population abundance and specific foraging strategies. Although the general trend showed a negative relationship between size and abundance, as expected, some taxa exhibited greater abundance than predicted for their average body masses. The analysis also indicated that functional singularity (rare functional strategies) is not associated with greater abundance. However, we identified specific combinations of functional traits associated with higher biomass in Trichoptera, such as anal claws, presence of a slime gland, fixed house builders and collector-filter feeding habits. These findings suggest that certain combinations of traits may favor the disproportionate abundance of some taxa.
Understanding the disproportionality of aquatic macroinvertebrates in size-density relationships in Atlantic Forest streams
Keywords: Macroinvertebrados; Riachos Neotropicais; Teoria metabólica; Redes tróficas; Diversidade funcional; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS